“Pulled Apart, Pushed Together”: Diversity and Unity within the Congress of South African Trade Unions - Brookes, Michael; Hinks, Timothy; Wood, Geoffrey; Dibben, Pauline; Roper, Ian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2004)
This is a study of horizontal and vertical solidarity within a national labour movement, based on a nationwide survey of members of affiliated unions of the Congress of South African Trade Unions. On the one hand, the survey reveals relatively high levels of vertical and horizontal solidarity, despite the persistence of some cleavages on gender and racial lines. On the other hand, the maintenance and deepening of existing horizontal and vertical linkages in a rapidly changing socio-economic context, represents one of many challenges facing organized labour in an industrializing economy. COSATU’s strength is contingent not only on an effective organizational capacity, and a supportive network linking key actors and interest groupings, but also on the ability to meet the concerns of existing constituencies and those assigned to highly marginalized categories of labour.